2021
DOI: 10.1021/acs.organomet.0c00738
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nitrogen-Rich Substrates by Low-Valent, Redox-Active Aluminum Species

Abstract: Reactivity of low-valent Al II species containing redox-active dpp-dad or dpp-Bian ligand (L a = dpp-dad = [(2,6-iPr 2 C 6 H 3 )NC(CH 3 )] 2 ; L b = dpp-Bian = 1,2-[(2,6-iPr 2 C 6 H 3 )NC] 2 C 10 H 6 ) toward nitrogen-rich substrates is described. Reactions of dialumanes [L 2− Al−AlL 2− ] (L a , 1a, or L b , 1b) with azides (Me 3 SiN 3 , BenzylN 3 ) or azobenzene at room temperature lead to the facile elimination of dinitrogen (in the case of azides) and formation of dimeric imido-complexes [L •− Al(μ 2 -NR) 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…Solution studies on the crystals of 2 in C 6 D 6 confirmed the above observation as the β‐CH 2 (TMP) protons were found to be split into three separate multiplets in the 1 H NMR spectrum (2H, 1H, and 1H respectively), of which two protons appear shielded at −0.02 (1H) and −0.30 ppm (1H) respectively (See Supporting Information, Figure S14) indicating the close interaction of the sodium centre to the axial H‐ atoms of the TMP moiety in the donor‐free aluminate. The structures of 2 and 2 a bear significance on the grounds of the paucity of structures of bisamido bridged sodium aluminates with only a few crystallographically characterised examples present in the literature from the Fedyushkin and Chivers groups [21a,b] …”
Section: Resultsmentioning
confidence: 99%
“…Solution studies on the crystals of 2 in C 6 D 6 confirmed the above observation as the β‐CH 2 (TMP) protons were found to be split into three separate multiplets in the 1 H NMR spectrum (2H, 1H, and 1H respectively), of which two protons appear shielded at −0.02 (1H) and −0.30 ppm (1H) respectively (See Supporting Information, Figure S14) indicating the close interaction of the sodium centre to the axial H‐ atoms of the TMP moiety in the donor‐free aluminate. The structures of 2 and 2 a bear significance on the grounds of the paucity of structures of bisamido bridged sodium aluminates with only a few crystallographically characterised examples present in the literature from the Fedyushkin and Chivers groups [21a,b] …”
Section: Resultsmentioning
confidence: 99%
“…An interesting possibility for controlling the reactivity of Al–Al species is the introduction of redox-active ligands at the Al centres, and a handful of low-valent aluminium compounds have been prepared with redox-active organic ligands. 13 However, the incorporation of classical redox-active organometallic substituents such as ferrocenyl groups has not been demonstrated. Redox-active ligands bound to a metal centre play an important role in controlling the reactivity of the complex, 14 and their nature depends on redox-active moieties, either bound as ligands or in the second coordination sphere of a metal cofactor, to catalyse challenging reactions.…”
Section: Introductionmentioning
confidence: 99%
“…It finds use in molecule activation, olefin polymerization, asymmetric transformations, coupling reactions, and other catalytic applications . Earlier, we had made a few attempts for investigation of reactivity of the gallium–dpp-bian system and found it useful for activation of small molecules and heteroallenes as well as for polymerization of cyclic ethers (Scheme ). Due to this peculiar cooperative capability of the gallylene [(dpp-bian)­Ga], we hypothesized its transition metal complexes (Scheme ) that consist of three reactive centers, a redox-active ligand, a main group low-valent metal atom, and a transition metal atom, to be useful for the activation of organic molecules.…”
Section: Introductionmentioning
confidence: 99%